The General Election Commission (KPU) Communication Model in Increasing Voter Participation in the Election of the Governor of Sumut 2018 in Labuhanbatu Selatan District - Sarino Sarino; Erwan Efendi; Anang Anas Azhar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to find out The General Election Commission (KPU) Communication Model in Increasing Voter Participation in the Election of the Governor of Sumut 2018. This research is included in qualitative research. Qualitative research is a social research which fundamentally relies on observing humans in their own domain and relating to those people who seek toreveal actual facts / phenomena that occur in the field. Based on the results of research that has been carried out with the title "Communication Model of the General Election Commission (KPU) in Increasing Voter Participation in the 2018 North Sumatra Governor Election in South Labuhanbatu Regency", the researchers concluded as follows: The General Election Commission of South Labuhanbatu Regency will collect data on the List of Candidates for Permanent Voters who will be given outreach. The General Election Commission of South Labuhanbatu Regency conducts outreach for novice voter candidates in high school equivalent to students who are already in class XII The General Election Commission of South Labuhanbatu Regency carried out the dissemination of the Governor Election to Farmers and Fishermen Communities. The General Election Commission of South Labuhanbatu Regency Strengthens the Synergy of the General Election Commission (KPU) with Local Community Organizations (Ormas). The General Election Commission of South Labuhanbatu Regency conducted socialization through audio and visual media.  The General Election Commission of South Labuhanbatu Regency uses the Question and Answer method, the community asks questions related to procedures and so on then the officer answers or vice versa .